nifH pyrosequencing reveals the potential for location-specific soil chemistry to influence N₂-fixing community dynamics - Collavino, Mónica Mariana (2014)
A dataset of 87 020 nifH reads and 16 782 unique nifH protein sequences obtained over 2 years from four locations across a gradient of agricultural soil types in Argentina were analysed to provide a detailed and comprehensive picture of the diversity, abundance and responses of the N₂-fixing community in relation to differences in soil chemistry and agricultural practices. Phylogenetic analysis revealed an expected high proportion of Alphaproteobacteria, Betaproteobacteria and Deltaproteobacteria, mainly relatives to Bradyrhizobium and Methylosinus/Methylocystis, but a surprising paucity of Gammaproteobacteria. Analysis of variance and stepwise regression modelling suggested location and treatment-specific influences of soil type on diazotrophic community composition and organic carbon concentrations on nifH diversity. nifH gene abundance, determined by quantitative real-time polymerase chain reaction, was higher in agricultural soils than in non-agricultural soils, and was influenced by soil chemistry under intensive crop rotation but not under monoculture. At some locations, sustainable increased crop yields might be possible through the management of soil chemistry to improve the abundance and diversity of N₂-fixing bacteria.